2023
DOI: 10.1002/bte2.20220060
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen reduction performance measurements: Discrepancies against benchmarks

Abstract: Oxygen electrocatalysis is crucial for renewable energy conversion and storage technologies. Specifically for proton exchange membrane fuel cells (PEMFCs), oxygen reduction reaction (ORR) is the primary reaction that determines performance and costs. The ORR activity and durability are commonly assessed using a rotating disk electrode (RDE). However,  there are numerous inconsistencies in the RDE measurements among researchers when comparing newly developed ORR catalysts to state‐of‐the‐art ones. These inconsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Similarly, it is reported that the activation energies for CO 2 RR in dry reforming of methane have been reduced 30% below the thermal activation by the plasmonic coupling effect of Pt and Au NPs. 76–78 Furthermore, the investigations also showed the abundance of multi-carbon compounds synthesized and favorable C–C coupling on the photoexcited Ag surface (Fig. 2a).…”
Section: Activity and Selectivity Regulations In Plasmonic Catalysismentioning
confidence: 82%
“…Similarly, it is reported that the activation energies for CO 2 RR in dry reforming of methane have been reduced 30% below the thermal activation by the plasmonic coupling effect of Pt and Au NPs. 76–78 Furthermore, the investigations also showed the abundance of multi-carbon compounds synthesized and favorable C–C coupling on the photoexcited Ag surface (Fig. 2a).…”
Section: Activity and Selectivity Regulations In Plasmonic Catalysismentioning
confidence: 82%
“…Phosphate- and carboxylate-rich compounds are the ligands that are considered to be designed for bone targeting. Few small drugs ( Hochdorffer et al, 2012 ; Cole et al, 2016 ; Tauro et al, 2017 ; David et al, 2019 ), macrocyclic chelators ( Minoshima et al, 2019 ; Zaman et al, 2023 ), fluorescent dyes ( Liu et al, 2008 ; Bao et al, 2015 ; Zaman et al, 2023 ), nucleic acids ( Liu et al, 2008 ), cyclodextrin ( Liu et al, 2008 ), fullerene C 60 ( Kubícek et al, 2005 )[230], proteins ( Kubícek et al, 2005 ), polymers, nanomaterials, and cells were conjugated to the ligands to endow these molecules and species with bone-homing properties ( Gonzalez et al, 2002 ).…”
Section: Nanotechnology In Cancer Diagnosismentioning
confidence: 99%
“…10,11 Besides, the standards established by the Department of Energy (DOE) are primarily for MEA testing. 12 Therefore, applying the MEA standards for RDE testing results in substantial inaccuracies in RDE measurements, making the RDE results less reliable. In this review, we discuss the differences in operating conditions and protocols between ORR measurements in half and full cells and propose potential perspectives to address this challenge for standard ORR evaluations.…”
Section: Introductionmentioning
confidence: 99%